KONDISI MASYARAKAT MISKIN DI KABUPATEN SEKADAU (Se-Kecamatan Sekadau) - B01109001, RICKY HERMANDUS (Jurnal Curvanomic, 2016)
The research entitled “Condition Of poor People In SekadauRegency (A Case Study In Sekadau Sub-Districts) aimed to find outcondition of characteristic social economy of poor people in Sekadauregency and to know local government’s effort to decrease proverty inSekadau regency.The research methodology was interview and questioners thedata, primary and secondary, was gathered from interviewingrespondents from staff of government office and local public figures bygiving them questioners and from available data in governmentinstitutions. The data was analyzed by purposive sampling.The research finding showed that the poor people in Sekadauregency were productive and have been working, by the salary wassmall and was enough to fulfill their daily needs. In addition, they hadvery low human resources such as low education, low skill, and low inhealth. The local government has tried to decrease the proverty byproviding some programs but they were not optimal and weretemporary especially in remote areas of Sekadau regency.Key words: suety, proverty, salary